2005
DOI: 10.1152/ajpgi.00372.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bolus transit patterns in healthy subjects: a study using simultaneous impedance monitoring, videoesophagram, and esophageal manometry

Abstract: transit patterns in healthy subjects: a study using simultaneous impedance monitoring, videoesophagram, and esophageal manometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 15 publications
5
77
0
6
Order By: Relevance
“…The relevance of the LPZ has been a subject of controversy. While for some bolus retention in this zone might be accepted as physiologic others consider bolus stasis in this zone pathologic 9,10 . A study in 6 healthy volunteers using HRM and videofluoroscopy found a wider LPZ possibly to be more likely associated with bolus stasis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of the LPZ has been a subject of controversy. While for some bolus retention in this zone might be accepted as physiologic others consider bolus stasis in this zone pathologic 9,10 . A study in 6 healthy volunteers using HRM and videofluoroscopy found a wider LPZ possibly to be more likely associated with bolus stasis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed strong correlation between impedance measurements and videofluoroscopy in assessing bolus transit in healthy adults. 14,21 Only one small study validated esophageal impedance method for bolus transit patterns in comparison with barium videoesophagram in 16 dysphagia patients, and still showed impedance monitoring as a valid transit test in dyspeptic patients with severe barium stasis. 22 However, studies using concurrent manometric and videofluoroscopic recording in symptomatic patients showed an excellent correlation between the findings from 2 tests.…”
Section: Discussionmentioning
confidence: 99%
“…Impedance parameters calculated for the evaluation of bolus transit using liquid and viscous swallows are: (1) total bolus transit time (between bolus entry at 20 cm above the LES and bolus exit at 5 cm above the LES); (2) bolus presence time (the interval between bolus entry and bolus exit at each impedance-measuring site); and (3) segmental transit times (the interval between bolus entry at a given level above the LES and bolus exit at the next most distal level) [10] . Swallows are classified as having: (1) [7] . 1 identified at one or more of the three distal impedancemeasuring sites.…”
Section: Mii: Clinical Aspectsmentioning
confidence: 99%
“…Studies using combined fluoroscopy and impedance have validated the convention that liquid bolus entry is characterized by a 50% drop in impedance at the recording site while bolus exit is characterized by a return to at least 50% of baseline [5,6] . Studies assessing the correlation between simultaneous barium videoesophagram and impedance revealed agreement in over 97% of swallows for determining normal bolus transit or retrograde escape and stasis [7] . Thus, this technique provides qualitative evidence of esophageal emptying.…”
Section: Introductionmentioning
confidence: 99%